TRANSFORMATION OF DIGITAL-BASED EDUCATION SUPERVISION IN THE AI ERA - Afdhalia, Shafia; Aziza; Kailul (Jurnal Ikhtibar Nusantara, 2026)
This study aims to analyze the transformation of digital-based educational supervision in the era of Artificial Intelligence (AI), including the shift from manual to digital supervision systems, the integration of AI in educational supervision, AI-based supervision models, and the opportunities and challenges of their implementation. The method employed in this study was a Systematic Literature Review (SLR) guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. A total of 22 national and international scientific articles published between 2020 and 2025 were selected and analyzed. The findings indicate that educational supervision has transformed from a conventional model into a technology-based digital supervision system utilizing online platforms, real-time monitoring systems, cloud-based data storage, and digital data analytics. The integration of Artificial Intelligence (AI) enables supervision processes to be conducted more objectively, efficiently, and data-driven through learning analytics, digital dashboards, and automated recommendation systems. AI-based supervision models have evolved into AI-assisted supervision, predictive supervision, real-time supervision, and hybrid intelligence supervision, which combines human intelligence with artificial intelligence. However, its implementation still faces several challenges, including limited technological infrastructure, low digital literacy, ethical and data privacy concerns, and resistance to change. This study concludes that digital and AI-based educational supervision has significant potential to improve effectiveness, efficiency, objectivity, and decision-making quality in education. Therefore, supportive policies, human resource capacity building, and adequate regulations are essential to ensure its successful and sustainable implementation.